Implementation of Parent Company's Liability for Bankruptcy Experienced by Subsidiary: Case in Indonesia - Annurdi; Budi Santoso; Hanif Nur Widhiyanti; Reka Dewantara (Finanse i Prawo Finansowe)
The purpose of the article. The article aims to reveal the existence of vacuum of norms regarding a group company in Indonesia, especially regarding the parent company's responsibility for bankruptcy experienced by its subsidiary.